Spectrum of ovarian tumors in a referral hospital in Nepal - Vaidya, S; Sharma, P; KC, S; Vaidya, SA (Journal of Pathology of Nepal, 2014)
Background: Ovarian tumors are common forms of neoplasia in women. Among cancers of the female genital tract, it ranks only below carcinoma of the cervix and the endometrium, but is responsible for approximately 50% of the deaths. They arise from different cell lineages and hence constitute a wide variety of neoplastic entities with diverse morphological and clinical manifestations. Materials and Methods: A descriptive study of 363 cases of ovarian tumors was carried out during a three year period from January 2011 to December 2013. Results: Of the 363 ovarian tumors, 293 (80.72%) cases were benign, 57 (15.70%) were malignant and 13 (3.58%) were borderline. Germ cell tumour was the most common class of tumour and seen in 187 (51.52%) cases, followed by surface epithelial in 158 (43.53%) cases. The age distribution of the patients ranged from 10-82 years with a median age of 33 years. Benign tumors were more common than malignant ones in all age groups. Conclusion: Most of the ovarian tumors in this study were of germ cell origin. The incidence of malignant germ cell tumors was also significantly higher than in other studies. Mature cystic teratoma was the most common benign tumour while serous carcinoma was the most common malignancy. The incidence of malignant germ cell tumors was higher compared to other studies. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10295 Journal of Pathology of Nepal (2014) Vol. 4, 539-543